Perceptions of Change and Migration Aspirations - Horzsa Gergely (European Countryside)
Based on a series of qualitative fieldwork in peripheral rural settlements of Hungary, this paper aims to explore the intertwined nature of development and migration by developing a theory-based methodology as a tool. Specifically, the goal is to understand how personal perceptions of local changes are connected to outwards mobility aspirations of rural dwellers. The series of fieldwork, conducted in 8 remote villages of Hungary in the period of 2014–2019 along with the 163, verbatim-transcribed semi-structured and in-depth interviews specifically engaged in understanding changes and migration goals, sets the ground for a detailed investigation of the topic. During the analytical process, a theory-based system is provided for the categorisation of respondents into migration aspiration groups. Differences and similarities based on personal perceptions of social change are then analysed in this distinction. Results show that both voluntary mobile and involuntary immobile people regard local changes as deterioration and development programmes as unsatisfactory, with the former group speaking in relative, contextual terms and the latter with the terminology of invariability, fixedness and hopelessness. Conversely, voluntary immobile respondents regard local changes as positive enabling (though not facilitating) factors of their desire to stay, while understanding their ineffective nature on local economy in general. This paper argues (im)mobility aspirations to be determined by similar freedom-maximizing strategies in all mobility groups, with different forms of freedom being preferred by the different groups. Consequently, to reach the goals of decreasing the depopulation of the countryside, public development policies are expected to enhance the forms of freedom preferred by people who desire to stay.